2001
DOI: 10.1037/h0087365
|View full text |Cite
|
Sign up to set email alerts
|

Do chimpanzees seek explanations? Preliminary comparative investigations.

Abstract: During the past decade, considerable effort has been devoted to understanding whether chimpanzees reason about unobservable variables as explanations for observable events. With respect to physical causality, these investigations have explored chimpanzees' understanding of gravity, force, mass, shape, and so on. With respect to social causality, this research has focused on the question of whether they reason about mental states such as emotions, desires, and beliefs. In the studies reported here, we explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 18 publications
1
40
2
Order By: Relevance
“…Like human children, young chimpanzees inspect and manipulate objects that do not function as expected in a familiar task, reflecting a foundation of causative understanding [28]. When adequate information about causation is apparent in problem-solving tests, young, wild-born chimpanzees ignore irrelevant information and improvise solutions [29].…”
Section: Introductionmentioning
confidence: 99%
“…Like human children, young chimpanzees inspect and manipulate objects that do not function as expected in a familiar task, reflecting a foundation of causative understanding [28]. When adequate information about causation is apparent in problem-solving tests, young, wild-born chimpanzees ignore irrelevant information and improvise solutions [29].…”
Section: Introductionmentioning
confidence: 99%
“…However, further analysis of this behavior strongly suggested that this was not due to internal representation of the events or insight as chimpanzees also will stack crates when no food is available, and are completely incapable of performing this task when a single crate was placed out of sight in an accessible corridor, suggesting that the act does not represent an intentional, planned sequence (Kohler 1925;Nissani 2004). Further research has suggested chimps have very limited ability to attribute causality to unseen forces (Povinelli and Dunphy-Lelii 2001), cannot distinguish intentional from unintentional actions (Povinelli 1997), probably cannot internally represent the mental state of others in any substantial fashion (Bering 2003), and likely lack the ability to search for reasons or meaning behind events (Bering 2003;Povinelli and Dunphy-Lelii 2001).…”
Section: Intelligence Of Monkeys and Apesmentioning
confidence: 88%
“…However, one issue that has not been explored is the extent to which the capacity to generate an explanation after an unexpected change PRESCHOOLERS' EXPLANATIONS 683 has occurred contributes to children's performance on false-belief-explanation tasks. This is an important issue given that both children's capacity to formulate explanations (e.g., Hickling & Wellman, 2001), and to seek out explanations when an unexpected event occurs (Povinelli & Dunphy-Lelii, 2001) increase with age. Because children's success on false-belief-explanation tasks hinges on each of these factors, it is surprising that their contribution to task performance has not been systematically explored.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%